Optical Remote Sensing Methods for Floating Marine Debris Detection – Review and Bibliography Analysis - Duplančić Leder, Tea; Leder, Nenad; Baučić, Martina; Bačić, Samanta (Transactions on Maritime Science, 2024)
In the last several decades, the disposal and accumulation of debris in the marine and coastal environment has been one of the biggest and fastest-growing threats to the health of the world's oceans. Marine debris is present in all marine habitats and represents a great danger to global environmental and human health. Therefore, this paper aims to support efforts to achieve Good Environmental Status with respect to marine debris in all oceans and seas. The application of optical remote sensing methods for floating marine debris detection was briefly reviewed and the bibliometric analysis of the professional and scientific literature elaborated upon. In the overview part, previously used marine debris detection methods have been listed. The WoSCC (Web of Science Core Collection) and Scopus databases were considered, and the R Studio Bibliometrix and Biblioshiny software tools used for bibliometric analysis. 209 documents that can be classified into 43 research fields were identified in the two databases. Approximately 20% of the documents were published in two journals: the Marine Pollution Bulletin and Remote Sensing. Marine debris research was mainly published in the USA, Portugal, Italy, the United Kingdom, Germany, and China. A total of 54 countries participated in the publication of documents and it should be emphasized that all countries have shown great interest in international cooperation during the scientific research on marine debris. Scientific research on marine debris was found to have increased significantly since 2017, which is highly important for the protection of the environment and human health.